Correct Answer - Option 4 : None of these

**Given:**

4 years ago, Father's age = 3 × Son's age

Sum of Father's age and Son's age = 64 years

**Calculation:**

Let the Father's present age and Son's present age be x years and y years respectively

According to the question

Four years ago, father's age = 3 × Son's age

⇒ (x − 4) = (y − 4) × 3

⇒ x = 3y − 8 ----(1)

After 4 years, Sum of Father's age and Son's age = 64

⇒ (x + 4) + (y + 4) = 64

⇒ x + y = 56

⇒ y = 56 - x ----(2)

Putting the value of y in equation (1), we get

x = 3y − 8

⇒ x = 3(56 - x) - 8

⇒ x = 3 × 56 − 3x − 8

⇒ 4x = 160

⇒ x = 160/4 = 40

**∴ The Father's present age is 40 years.**